Frequency of detection and phylogenetic analysis of porcine circovirus 3 (Pcv-3) in healthy primiparous and multiparous sows and their mummified fetuses and stillborn - Saporiti, Viviane (2020)
Porcine circovirus 3 (PCV-3) has been suggested as a putative causal agent of swine reproductive disease. A number of different studies have pointed out this association, but there is still a lack of information regarding the normal rates of PCV-3 infection in farms with normal reproductive parameters. The objective of the present study was to assess the frequency of PCV-3 detection in primiparous and multiparous sows and in tissues from their respective fetuses from farms with average reproductive parameters. Sera from 57 primiparous and 64 multiparous sows from 3 different farms were collected at two time points. Brain and lung tissues from 49 mummies and 206 stillborn were collected at farrowing. Samples were tested by PCR, and when positive, quantified by quantitative PCR. Thirty-nine complete genomes were obtained and phylogenetically analyzed. All sera from multiparous sows were negative, while 19/57 (33.3%) primiparous sows were PCV-3 PCR positive. From the 255 tested fetuses, 86 (33.7%) had at least one tissue positive to PCV-3. The frequency of detection in fetuses from primiparous sows (73/91, 80.2%) was significantly higher than those from multiparous ones (13/164, 7.9%). It can be concluded that PCV-3 is able to cause intrauterine infections in absence of overt reproductive disorders.